1986
DOI: 10.1093/jac/17.4.441
|View full text |Cite
|
Sign up to set email alerts
|

The activity of BMY 28142 a new broad spectrum β-lactamase stable cephalosporin

Abstract: The in-vitro activity of BMY 28142, an iminomethoxy, aminothiazolyl cephalosporin containing a methyl pyrrolidinio C-3 was compared with that of cefotaxime, ceftazidime, aztreonam, imipenem and tobramycin against various bacteria. BMY 28142 was the most active agent tested against the Enterobacteriaceae inhibiting 90% at less than or equal to 1 mg/l. The in-vitro activity of BMY 28142 was equal to or superior to cefotaxime against the highly susceptible members of the Enterobacteriaceae and several-fold superi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 0 publications
3
26
0
1
Order By: Relevance
“…Cefepime is well tolerated and appears to be comparable to ceftazidime in treatment of skin or wound infections and nosocomial UTIs in hospitalized patients. Although ceftazidime is more active in vitro against P. aeruginosa than cefepime is (2,5,7), clinical and bacteriologic responses for this pathogen were equivalent in this study. Larger studies are required to confirm the relative efficacies of cefepime and ceftazidime in diabetic subjects with infection due to P. aeruginosa.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Cefepime is well tolerated and appears to be comparable to ceftazidime in treatment of skin or wound infections and nosocomial UTIs in hospitalized patients. Although ceftazidime is more active in vitro against P. aeruginosa than cefepime is (2,5,7), clinical and bacteriologic responses for this pathogen were equivalent in this study. Larger studies are required to confirm the relative efficacies of cefepime and ceftazidime in diabetic subjects with infection due to P. aeruginosa.…”
Section: Discussionmentioning
confidence: 56%
“…Strains of Enterobacter spp., S. marcescens, and Citrobacterfreundii which may be resistant to other cephalosporins such as ceftazidime and cefotaxime are frequently very susceptible to cefepime (3,(5)(6)(7). During the course of this study, one prospective subject was found to have a surgical wound infected with ceftazidime-resistant, cefepime-susceptible Enterobacter cloacae and was compassionately treated for 7 days with cefepime, which effected a cure of the infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether cefepime can be used is unsettled. Cefepime is a poor inducer of AmpC ␤-lactamase, rapidly penetrates through the outer cell membrane, and is little hydrolyzed by the enzyme (232,283), so many AmpC-producing organisms test cefepime susceptible with a conventional inoculum (see Table 6 for examples). If a 100-fold-higher inoculum is used, however, cefepime MICs increase dramatically for some AmpC producers, suggesting caution in its use (154,256), and some strains are frankly resistant (238).…”
Section: Treatment Of Ampc-producing Organismsmentioning
confidence: 99%
“…Cefepime, with its dipolar charge, has the advantage of penetrating bacterial outer membranes more rapidly than 3 rd generation cephalosporins, readily reaching its target and avoiding β-lactamase inactivation. Additionally, Cefepime has a reduced affinity for β-lactamases and also appears to be a poor inducer of AmpC β-lactamases (11,12 The metabolic versatility for which Pseudomonas are so renowned. It can tolerant to wide variety of physical conditions, including temperature resistant to high concentration of salt and days, weak antiseptics and many commonly used antibiotics.…”
Section: Introductionmentioning
confidence: 99%